Estudo da atividade citotóxica, antitumoral e determinação do perfil tóxico de complexos de rutênio(II)/aminoácidos em células do tumor de Ehrlich in vitro e in vivo - Mello, Francyelli Mariana dos Santos (2014)
Ruthenium complexes represent a new alternative anticancer chemotherapeutics, with activity against several types of cancer, including those resistant to cisplatin, low toxicity and selectivity for tumor cells. The new amino acids/ruthenium(II) complexes (RuAA) w ere tested against Ehrlich ascitic tumor (TAE) cells, murino mammary carcinoma, in vitro and in vivo . The concentration that inhibits 50% of cell viability (IC 50 ) was determined by MTT assay to TAE and L929 cells. Based on the values of IC50 value was determined selective potential of RuAA and selected two complexes most promising, estimated the LD50 (median lethal dose). The toxicological profile of RuMet and RuTrp was determined by acute oral toxicity following the class method, hippocratic screening, and determination of the genotoxic potential evaluated by the comet assay. The effectiveness of the antitumor potential of RuMet and RuTrp was established by the percentage of inhibition of tumor growth and increased survival in vivo after 24 hours of inoculation of TAE. Swiss mice were treated at doses of 2 and 6 mg/kg/day v.ip for 7 days. Hippocratic screening, assessment the viability of TAE cells after treatment, and hematological and biochemical parameters also were performed. Complexes RuAA are cytotoxic to TAE cells in vitro with IC50 value ranging from 8.70 to 90.41 µM. RuMet and RuTrp complexes showed selective and potent for tumor cells. The estimated in vitro LD50 for RuMet and RuTrp were higher than 1000 mg/kg, and in vivo these complexes have low toxicity and genotoxicity. RuMet and RuTrp complexes showed moderate to high antitumor activity compared to the vehicle group, with increased median survival time (from 23.6 to 27.4 days) and percentage increase in survival (from 31 to 52%). RuMet and RuTrp increased the percentage of cells killed by apoptosis initial. There were no signs of toxicity or changes in the behavior of animals. Hematological parameters showed alterations in platelet count at doses of 6 mg/kg/day complexes of RuMet and RuTrp. The dosage of lactate dehydrogenase showed a change in the assessment of biochemical parameters. Complexes of RuMet and RuTrp are efficient, selective and potent for ascitic tumor cells presenting in vitro cytotoxicity and in vivo antitumor activity, with increased survival time, with low toxicity and genotoxicity.